2021
DOI: 10.12659/aot.929279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcineurin Inhibitors and Mammalian Target of Rapamycin Inhibitors on the Course of COVID-19 in Kidney Transplant Recipients

Abstract: Coronavirus disease 19 (COVID-19) has been an ongoing pandemic since December 2019. Unfortunately, kidney transplant recipients are a high-risk group during the disease course, and scientific data are still limited in this patient group. Beyond the dosage of immunosuppressive drugs, pharmacological immunosuppression may also alter the infection response in the COVID-19 course. The effects of immunosuppressive agents on the development and process of infection should not be decided only by determining how poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…tacrolimus has shown a more significant inhibitory effect on cellular immune responses than everolimus, but both inhibit humoral immune responses equally. as a result, tacrolimus can be effective in COVID-19 treatment due to its ability to attenuate the production of T-related cytokines [ 5 ]. Oral administration of sapanisertib (INK0128; INK128) blocks mTORC1 and mTORC2 [ 9 ].…”
Section: Metformin Tacrolimus Sapanisertib and Pp-242: Mtor Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…tacrolimus has shown a more significant inhibitory effect on cellular immune responses than everolimus, but both inhibit humoral immune responses equally. as a result, tacrolimus can be effective in COVID-19 treatment due to its ability to attenuate the production of T-related cytokines [ 5 ]. Oral administration of sapanisertib (INK0128; INK128) blocks mTORC1 and mTORC2 [ 9 ].…”
Section: Metformin Tacrolimus Sapanisertib and Pp-242: Mtor Inhibitorsmentioning
confidence: 99%
“…Rapamycin decreases CD19 + CD27 + memory B lymphocytes and induces their differentiation to plasma cells. It is also shown that rapamycin (by inducing HLA-DR expression) was more effective in reducing the population of B lymphocytes than tacrolimus [ 5 ]. In the light of such investigations, it can be concluded that rapamycin can play a role in intervening in the production of antibodies in COVID-19 by reducing the population of B lymphocytes.…”
Section: Inhibitory Drugs: Foes or Allies?!mentioning
confidence: 99%
See 1 more Smart Citation
“…PRAS40 blocks binding of p70 ribosomal S6 kinase (p70S6K) and the eukaryotic initiation factor 4E (eIF4E)-binding protein 1 (4EBP1) to Raptor that can affect mTORC1 activity [165,166]. Rapamycin mTORC1 [24] as well inhibits activation of mTORC1 [162,[167][168][169][170]. mTORC2 has some different components when compared to mTORC1 [171].…”
Section: Circadian Clock Genes and The Mechanistic Target Of Rapamycinmentioning
confidence: 99%
“…mTORC1 activity is controlled through a number of pathways that includes PRAS40 by blocking the association of p70 ribosomal S6 kinase (p70S6K) and the eukaryotic initiation factor 4E (eIF4E)-binding protein 1 (4EBP1) with Raptor [167,168]. Rapamycin is an agent that can inhibit mTOR activity [164,[169][170][171][172]. Rapamycin blocks the activity of mTORC1 through its association with immunophilin FK-506-binding protein 12 (FKBP12) that attaches to the FKBP12 -rapamycin-binding domain (FRB) at the carboxy (C) -terminal of mTOR to impede the FRB domain of mTORC1 [4].…”
Section: The Mechanistic Target Of Rapamycin (Mtor) and Autophagymentioning
confidence: 99%